2014
DOI: 10.1161/strokeaha.113.004483
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in Experimental Cerebral Amyloid Angiopathy and the Risk of Secondary Intracerebral Hemorrhage

Abstract: Background and Purpose-Intracerebral hemorrhage (ICH) is the most adverse event of thrombolysis in ischemic stroke.Cerebral amyloid angiopathy increases the risk for spontaneous lobar ICH. Although thrombolysis may be performed in cerebral amyloid angiopathy-affected patients, there is still little knowledge available on the risk for secondary ICH. Methods-We investigated the effect of recombinant tissue-type plasminogen activator on experimental ischemic stroke in APP23 transgenic mice (n=18) and wild-type li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In a meta‐analysis of patients with IS treated with thrombolysis, 9% of patients with CMBs experienced a symptomatic ICH after thrombolysis compared to 4% without CMBs . Two studies examined the effect of tPA in aged APP23 transgenic mouse models of CAA and found a higher risk of ICH in the CAA‐affected brains . One of these studies also examined mortality and functional outcomes and found no differences in APP23 mice compared to control animals .…”
Section: Management Of Acute Ischaemic Strokementioning
confidence: 99%
See 2 more Smart Citations
“…In a meta‐analysis of patients with IS treated with thrombolysis, 9% of patients with CMBs experienced a symptomatic ICH after thrombolysis compared to 4% without CMBs . Two studies examined the effect of tPA in aged APP23 transgenic mouse models of CAA and found a higher risk of ICH in the CAA‐affected brains . One of these studies also examined mortality and functional outcomes and found no differences in APP23 mice compared to control animals .…”
Section: Management Of Acute Ischaemic Strokementioning
confidence: 99%
“…Two studies examined the effect of tPA in aged APP23 transgenic mouse models of CAA and found a higher risk of ICH in the CAA‐affected brains . One of these studies also examined mortality and functional outcomes and found no differences in APP23 mice compared to control animals .…”
Section: Management Of Acute Ischaemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…However, it benefits only a small proportion of patients due to the limited thrombolysis window and the adverse reactions of thrombolytics (2,3). In addition, recanalization may cause severe cerebral ischemia-reperfusion (I/R) injury in the local region (4,5). Accumulating evidence has suggested that inflammatory and oxidative damage serves an important role in cerebral I/R injury (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem, 10 µm coronal cryosections were cut at 400 µm intervals and stained with hematoxylin–eosin–saffron (H&E) staining accordingly to previous protocols [19]. …”
Section: Methodsmentioning
confidence: 99%